Pendampingan Senam Jantung Sehat untuk Meningkatkan Kesehatan Masyarakat di Desa Doulu Kabupaten Karo - Julius Boy Nesra Basgimata Barus; Janwar Frihasan Sinuraya; Jusup Roy Tamba; Josua; Rafael Mey Hagata Sembiring (EDUPEDIA Publisher, 2024)
The aim of the socialization of healthy heart exercise in an effort to improve community fitness and health in Doulu Village, Karo Regency, North Sumatra Province is to improve community health through heart exercise and improve social relations within the community. public. The method used in this activity is a customized socialization method that is tailored to the situation analysis and needs of the target audience. The steps taken in this activity include approaching and collaborating with the community in Doulu Village, Karo Regency, North Sumatra Province, as well as observing and educating the community about healthy heart exercise material. This activity took place in the field in Doulu Village, Karo Regency. The socialization activity was carried out once, namely on October 2 2023. The aim of this cardiovascular exercise socialization activity is to provide knowledge about fitness and health through cardiac exercise, as well as provide skills in managing material related to cardiac exercise, with the aim of making it a weekly activity.